2022
DOI: 10.4103/jehp.jehp_1801_21
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of physiotherapy students' perception about blended learning with online learning during COVID-19 pandemic: A mixed method of study

Abstract: BACKGROUND: The COVID-19 pandemic has affected face-to-face teaching across the globe. The sudden shift in learning methods has impacted learning experiences significantly. Students' perception about online compared to blended learning might affect learning. The objective of this study was to evaluate physiotherapy students' perception of blended compared to online learning. MATERIALS AND METHODS: This mixed-method study documents physiotherapy students' perception abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Most students in our study were in favour of the continuation of blended learning post-COVID-19 pandemic, similar to the findings from the UK. 65,74 In addition, similar findings were reported from studies that were conducted across developed and developing countries including Sweden, 83 Bahrain, 67 Kazakhstan, 84 Saudi Arabia, 85 Kenya, 86 India, 87 Malaysia 88 and Bangladesh. 3 This is because blended learning offers many benefits to teachers and students including continued learning even with the closure of physical classes.…”
Section: Discussionsupporting
confidence: 70%
“…Most students in our study were in favour of the continuation of blended learning post-COVID-19 pandemic, similar to the findings from the UK. 65,74 In addition, similar findings were reported from studies that were conducted across developed and developing countries including Sweden, 83 Bahrain, 67 Kazakhstan, 84 Saudi Arabia, 85 Kenya, 86 India, 87 Malaysia 88 and Bangladesh. 3 This is because blended learning offers many benefits to teachers and students including continued learning even with the closure of physical classes.…”
Section: Discussionsupporting
confidence: 70%
“…Perception was often framed in terms of student opinion, acceptability, or attitude. Examples include perception of mobile learning [ 32 , 33 ], perception of online formative assessment [ 38 ], and perception of blended learning [ 39 ]. A few studies examined perception as part of a qualitative analysis (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Swaminathan et al. (2021) conducted a study on 158 entry‐level nursing graduate students in Chennai, India, and found that the majority of them are confident in accessing internet information. Willingness to study online, prior experience with distance education, and perceived benefits of the online component may all impact a learner's readiness for lifelong learning.…”
Section: Discussionmentioning
confidence: 99%